Evaluation of P-Wave Dispersion, Ventricular Functions, and Atrial Electromechanical Coupling in Children with Type 1 Diabetes Mellitus - Aydın Şahin, Derya; İrdem, Ahmet and Kervancıoğlu, Mehmet and Başpınar, Osman and Sucu, Murat and Keskin, Mehmet and Kılınç, Metin (European Journal of Therapeutics, 2023)
Objective: The present study aimed to evaluate ventricular diastolic function, inter- and intra-atrial conduction delay, and P wave dispersion in pediatric patients with type 1 diabetes mellitus (DM). Methods: This study comprised 30 pediatric patients with type 1 DM and 30 healthy children served as the control group. P wave dispersion (Pd )was measured on a 12-channel ECG. Both systolic and diastolic functions of both ventricles were evaluated using conventional and tissue doppler imaging (TDI) echocardiography (ECHO). Atrial electromechanical delay was measured using TDI accompanied with electrocardiography (ECG). Results: On conventional transthoracic echocardiography (ECHO), the mitral E/A ratio and isovolumetric relaxation times (IVRT) were different between the patients with type 1 DM and the control group (1.67±0.46 vs. 1.95±0.43, p=0.017 and 74.5±7.0 vs. 63.3±5.2, p<0.001, respectively). On TDI, LV septal peak systolic (Sm) and early diastolic (Em) velocities and Em/Am ratio were found to be significantly lower in the patients with type 1 DM than in the control group (p=0.047, p=0.003, and p=0.001, respectively). Regarding atrial electromechanical conduction, prolongation was detected in PA lateral, PA septal, PA tricuspid, and inter-atrial (PA lateral–PA tricuspid) and intra-atrial (PA septal–PA tricuspid) conduction delay (p<0.001, p<0.001, p<0.001, p<0.001, and p<0.05, respectively). Conclusion: Our findings suggest that intra- and inter-atrial conduction delay, p wave dispersion, and ventricular diastolic functions are abnormal in patients with type 1 DM.